Pengaruh Harga, Persepsi Resiko, dan Promosi terhadap Keputusan Pembelian pada E-Commerce Tiktok Shop: Studi Kasus Mahasiswa Universitas Tanjungpura - Kristianty, Cesilia Monika; Kurniawan, Rudy; Ginting, Rafles (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out the influence of price, preception of risk, and promotion on purcashing decisions using different methods. The research was conducted at Tanjungpura University, Pontianak, with a sample 0f 60 respondents, and used an approach, namely purposive sampling based on users. Tiktok application and those who have made purchases using the Tiktok Shop. In this research, quantitative methods were used. The analysis used is regression analysis, multiple linear which is a measuring tool for understanding the relationship between variables in predicting a value on a variable based on the result studied are proce, pereception of risk, and promotion that consumers can experience in product marketing, all of which influence the purchasing decisions of Tiktok Shop consumers. For each variable, the independent variable, such as setting a price, has a very positive influence on consumers purchasing decisions, perception of risk only has little influence on purchasing decisions because it is not very profitable. Anda finally, promotion have a very positive infience on purchasing decisions because advertising that provides its own value and start power for consumers becomes a purchasing decision for consumers.